Representações sociais sobre a soropositividade (re)produzida no discurso de pessoas vivendo com hiv/aids: uma análise crítica em perspectiva dialético-relacional - Lima, Fernando Henrique Rodrigues de (2023)
I place this work in the field of research on the study of language from a critical perspective in a theoretical-methodological interface established between Applied Linguistics and Social Psychology, with the aim of analyzing the social representation (SR) of seropositivity (re)produced in discourse of People Living with HIV/AIDS (PLHA) (as well as associated individuals) in selected posts in a discussion group on the digital social network Facebook. To achieve this objective, I articulate the assumptions of Critical Discourse Analysis (CDA), more specifically the dialectical-relational approach of Fairclough (2001), with the Theory of Social Representations, more specifically with the approaches of Moscovici (1976, 2007) and Jodelet (1984, 1991, 2001). I add to this interface, the proposal for investigating events on the WEB, according to the studies by Recuero (2010), Araújo (2006), among others. From a methodological point of view, we undertook a Discursive Approach to Social Representations (ADRS), of a qualitative ethnographic nature and, with the support of the Iramuteq software, I analyzed a corpus made up of posts from the largest group on the network (SOROPOSITIVOS – BRASIL E O MUNDO – RELACIONAMENTO E INFORMAÇÃO), written during the month of January 2020. In the aforementioned analysis, I assume the data interpretation procedure in three stages, namely: (i) textual analysis, focusing on the lexical choices that indicate the process of ( re)production of the social representation in question; (ii) discursive analysis, describing the conditions of production, distribution and consumption of texts involved in the practice under debate; and (iii) social practice, investigating the ideology and hegemonic power relations embedded in the analyzed discourse. The results of the analyzes show that, from the point of view of the text, four semantic nuances (abnormality, fear, unpronounceable and loneliness) manifest themselves based on the evidence highlighted by the program; from the point of view of discursive practice, it was observed that texts are produced, distributed and consumed through the post discursive genre, with access restricted to group members as it is a closed environment for debating topics that touch on delicate issues, from an emotional point of view, for its members; from the point of view of social practice, there was a manifestation of conservative ideology that marginalizes PLHA individuals within a hegemonic discourse supported by a society condescending to this social representation.